Metaphors in search of a target: the curious case of epigenetics - Stelmach, Aleksandra; Nerlich, Brigitte (Taylor & Francis, 2015)
Carrying out research in genetics and genomics and communicating about them would not be possible without metaphors such as "information," "code," "letter" or "book." Genetic and genomic metaphors have remained relatively stable for a long time but are now beginning to shift in the context of synthetic biology and epigenetics. This article charts the emergence of metaphors in the context of epigenetics, first through collecting some examples of metaphors in scientific and popular writing and second through a systematic analysis of metaphors used in two UK broadsheets. Findings show that while source domains for metaphors can be identified, such as our knowledge of electrical switches or of bookmarks, it is difficult to pinpoint target domains for such metaphors. This may be indicative both of struggles over what epigenetics means for scientists (natural and social) and of difficulties associated with talking about this, as yet, young field in the popular press.